ANALISIS PEMAHAMAN KONSEP SISWA BERDASARKAN TEORI APOS DALAM MATERI BILANGAN BULAT DI SMP - Adilla, Rizki; Jamiah, Yulis; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis qualitative research aims to find out the understanding of student concepts based on APOS theory in integer material.The method used is descriptive. The main aspect that will be explained in this research is the understanding of student concepts based on APOS theory in integer material in the SMP Negeri 3 Sungai Raya class VII. APOS theory can be used to identify student understanding of concepts in integer material which will later be described in four stages, namely the action, process, object and scheme stage. The subject of this research consists of 6 students class VII A SMP Negeri 3 Sungai Raya who have different abilities, namely high, medium and low ability. The result of this research showed the students who are in excellent category is in the stage of the scheme, this can be seen when students can combine several integer concepts. Students who are in low and medieval category is in the action stage, this can be seen when students can fill in the instructions given correctly.Keywords: APOS Theory, Concept Understanding